From Deprived to Revived: Religious Revivals as Adaptive Systems - Heimola, Mikko (Religion and reason, 2013)
What is the exact nature of the link between religion and social cohesion? This book describes how fluctuations in socioeconomic environment can create a process where ritual behavior works to alleviate uncertainties in social commitment. A case study of Finland’s 19th-century Christian revivals illustrates this process. This volume is particularly relevant to those interested in the role of religion in human evolution and in organizing society.